Analog IC Reliability in Nanometer CMOS - Maricau, Elie; Gielen, Georges (Analog Circuits and Signal Processing, 2013)
This book focuses on modeling, simulation and analysis of analog circuit aging. First, all important nanometer CMOS physical effects resulting in circuit unreliability are reviewed. Then, transistor aging compact models for circuit simulation are discussed and several methods for efficient circuit reliability simulation are explained and compared. Ultimately, the impact of transistor aging on analog circuits is studied. Aging-resilient and aging-immune circuits are identified and the impact of technology scaling is discussed.   The models and simulation techniques described in the book are intended as an aid for device engineers, circuit designers and the EDA community to understand and to mitigate the impact of aging effects on nanometer CMOS ICs.   ·         Enables readers to understand long-term reliability of an integrated circuit; ·         Reviews CMOS unreliability effects, with focus on those that will emerge in future CMOS nodes; ·         Provides overview of models for key aging effects, as well as compact models that can be included in a circuit simulator, with model parameters for advanced CMOS technology; ·         Describes existing reliability simulators, along with techniques to analyze the impact of process variations and aging on an arbitrary analog circuit.